Perancangan Aplikasi Pemesanan MUA Berbasis Web di Semarang Barat Menggunakan Agile Scrum - Dina, Annisa Nur; Razaq, Jeffri Alf (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
A web-based Make Up Artist (MUA) booking application prototype has been designed and developed for independent MUAs in West Semarang, utilizing the Agile Scrum method. This study stems from the difficulties prospective clients face in finding MUAs and the lack of service and domicile information, compounded by manual booking methods leading to scheduling irregularities. The objective is to provide an efficient and integrated online booking information system solution for MUA services. The methodology employed is Agile Scrum, with qualitative data collection through literature review and competitor analysis to identify necessary functional and non-functional requirements. A prioritized list of system features and functionalities has been compiled, serving as the basis for each Agile Scrum development sprint. The prototype successfully implemented core features such as registration, login, profile management, MUA and customer dashboards, MUA search, service booking, payment flow (COD/Transfer/QRIS), booking status notifications, MUA schedule management, admin dashboard, booking history, and MUA portfolio pages. While most core features function effectively, the booking cancellation feature still requires further improvement due to integration conflicts. This study concludes that the application successfully analyzed functional and non-functional requirements and implemented the aforementioned core features. The research contributes by providing an efficient and integrated online booking information system solution for MUA services, addressing information and digital booking management issues, particularly in the West Semarang area, and demonstrating the potential for dynamic adaptation through Agile Scrum.